Women's issues. - A. Hamid, Siti Zubaidah (1992)
Chemical dependence in women cannot be ignored anymore because it is affecting marriages, children and places of work of women. At least 2 million women are addict and many more experience drug related problems. (Wilsnack, S.C. 1984}. Yet, despite the scale of the problem, it is only in the last decade that there has been significant focus on the problems.